Frankenstein - Horton, Robert, 1958- (Cultographies., 2014)
James Whale's Frankenstein (1931) spawned a phenomenon that has been rooted in world culture for decades. This cinematic Prometheus has generated countless sequels, remakes, rip-offs, and parodies in every media, and this granddaddy of cult movies constantly renews its followers in each generation. Along with an in-depth critical reading of the original 1931 film, this book tracks Frankenstein the monster's heavy cultural tread from Mary Shelley's source novel to Internet chat rooms.